Transvaginal Ultrasound-Guided Aspiration of Pelvic Abscesses - P. J. Corsi; S. C. Johnson; B. Gonik; S. L. Hendrix; S. G. McNeeley; M. P. Diamond (Hindawi Limited, 1999)
Objective: To assess the utility of a less invasive approach to the care of women with a pelvic abscess, we retrospectively reviewed the outcome of women with pelvic abscesses managed by transvaginal ultrasound-guided aspiration.